Sosialisasi Penggunaan Kunyit Sebagai Bahan Uji Deteksi Borak Di Desa Padang Kuas - Indah, Zahara; Syafryadin, Syafryadin; Pratama, M. Iqbal Liayong; Melo, Ramla Hartini (Universitas Negeri Gorontalo, 2023)
The socialization activity on using turmeric as a borax detector in Padang Kuas Village is significant because food safety is vital to maintaining the community's health and quality of life. This activity aims to increase public awareness and knowledge about the dangers of borax in food and teach the use of turmeric as a natural and safe borax detector. The activity method involves the delivery of comprehensive materials and the practice of testing borax using turmeric and is accompanied by a question-and-answer session and evaluation. This activity showed a significant increase in community knowledge about borax and awareness of its dangers, as well as an increase in the practice of testing borax with turmeric in their daily environment. The follow-up of this activity will involve periodic evaluations to monitor the effectiveness of the outreach program, ongoing assistance, and dissemination of information about using turmeric as a borax detector regularly to ensure continued awareness and community participation in maintaining food safety and creating a safer and healthier environment.